Focus on community: directions for nursing knowledge development - Kulbok, Pamela A; Gates, Marie F; Vicenzi, Angela E; Schultz, Phyllis R (Journal of Advanced Nursing, 1999)
Nurses are challenged to advance the theoretical foundations of community practice. This paper offers ideas on what-has been done and what needs to be done to meet this challenge. Within a community health nursing perspective, the paper defines community, proposes an integrated knowledge development framework that focuses on community, analyses contemporary theoretical and philosophical foundations of community in nursing, considers three worldviews in which nursing can be framed, and examines parameters for knowledge development for the future.
Keywords: Community; Community Health Nursing; Community health nursing; Humans; Knowledge; Knowledge development; Nursing; Nursing Theory; Nursing theory; Philosophy; Post-modernism; Professional Practice; World-view; article; community health nursing; dept.nur; human; knowledge; nursing; nursing theory; professional practice